Effect of Stem Cell Augmented Micronized Allograft on Arthrodesis in the Ankle and Foot. Issue 3 (14th September 2018) - Fantry, Amanda; Bowler, Joshua; Daoud, Yahya; Brodsky, James
Category: Basic Sciences/Biologics Introduction/Purpose: Both primary and revision arthrodesis are mainstays of foot and ankle surgery. Many studies have investigated the effect of autograft, varying forms of bone graft substitutes, and of biologic agents on bone healing, including in the setting of arthrodesis. A commercially available stem cell augmented micronized allograft (Via Graft®) is comprised of micronized (100-300 microns) allograft bone with marrow-isolated adult multilineage inducible cells (MIAMI cells). It has been proposed as an alternative to autograft and as an adjunct to arthrodesis. We present a series of 86 patients with minimum one-year follow-up who underwent either primary or revision arthrodesis with Via Graft®, with or without additional graft. Methods: Between 2015 and 2016, 86 patients treated with Via Graft® were identified with minimum one-year follow-up. Data was collected including demographic information, BMI, smoking history, medical comorbidities; indication for fusion (including Charcot arthropathy, posttraumatic arthritis, rheumatoid arthritis, AVN, congenital anomalies, neuromuscular disorders, revision surgery, post-infectious, previous total ankle arthroplasty, posterior tibial tendon dysfunction); procedure performed (ankle, hindfoot, midfoot, or forefoot fusion), number of joints fused, use of additional graft, radiographic union, and complications. Fusion was evaluated based upon radiographic or CT evidence of osseous bridging. The unit of the analysis was the joint. Generalized Linear Mixed Model (GLMM) was utilized to evaluate the association between fusion and the data set described above. Statistical analyses were performed using SAS® 9.4. Results: 191 joints were fused in 86 patients (F: 48, M: 38). Mean age was 58.7 years, mean follow-up was 15.8 months. Radiographic union was achieved in 163/191 (85.3%) joints. Age, gender, smoking status, presence of diabetes, history of Charcot, revision fusion, or use of cancellous autograft or allograft demonstrated no statistically significant differences in fusion rates. Intramedullary talocalcaneal arthrodesis (IMTCA), with or without additional joints fused simultaneously (p=.001), use of structural allograft (most commonly femoral head)(p<.001), structural autograft (p=.001), history of previous TAA (p<.0001), and history of AVN (p=.042) demonstrated statistically significant rates of nonunion, despite use of Via Graft® (Table 1). Conclusion: This study is the largest series to date of Via Graft® augmentation of arthrodesis. Lower union rates were found to be associated with patients undergoing hindfoot fusion with an IMTCA with or without additional joints fused, a history of failed total ankle replacement or AVN of the talus, and use of femoral head allograft. However, this preliminary study requires further analysis given the difficult and salvage nature of these cases. As bony union is multifactorial, the selection of bone graft and biologic agents is an important factor, but may not be sufficient to overcome the biology of the host.